Dimensi Pembangunan Berkelanjutan (Sustainable Development) Perspektif Al-Quran dan Hadits - Sulaeman; Hasan Ridwan, Ahmad (PT. Alahyan Publisher Sukabumi, 2023)
This paper explores the concept of sustainable development from an Islamic perspective based on the QThis paper explores the concept of sustainable development from an Islamic perspective based on the Quran and Hadith. Sustainable development aims to meet the current generation's needs without compromising the future generation's capacity through economic growth, social justice, and environmental protection. However, academic discourse integrating these three pillars from an Islamic viewpoint is limited. Therefore, this paper analyses relevant Quranic verses and Hadiths to formulate a comprehensive sustainable development concept in Islam encompassing those key pillars. Content analysis finds Islamic sustainable development contains four main complementary dimensions: (1) comprehensive social development considering individual and societal wellbeing, (2) economic development focused on financing sources and economic potential mobilization, (3) legal and policy development to facilitate and protect development processes, and (4) stability and security as prerequisites for development. These dimensions align with the human role on Earth to prosper while safeguarding sustainability. Development must promote justice through balancing current and future generation interests. Hence, Islamic sustainable development integrates spiritual, social, economic, and environmental aspects. This concept can enrich contemporary Islamic scholarship on the issue and serve as an alternative framework for Muslim-majority countries to formulate policies towards welfare and sustainability.ran and Hadith. Sustainable development aims to meet current generation needs without compromising future generation capacity through economic growth, social justice and environmental protection. However, academic discourse integrating these three pillars from an Islamic viewpoint is limited. Therefore, this paper analyses relevant Quranic verses and Hadiths to formulate a comprehensive sustainable development concept in Islam encompassing those key pillars. Content analysis finds Islamic sustainable development contains four main complementary dimensions: (1) comprehensive social development considering individual and societal wellbeing, (2) economic development focused on financing sources and economic potential mobilization, (3) legal and policy development to facilitate and protect development processes, and (4) stability and security as prerequisites for development. These dimensions align with the human role on Earth to prosper it while safeguarding sustainability. Development must promote justice through balancing current and future generation interests. Hence, Islamic sustainable development integrates spiritual, social, economic and environmental aspects. This concept can enrich contemporary Islamic scholarship on the issue and serve as an alternative framework for Muslim-majority countries to formulate policies towards welfare and sustainability.